Beautiful uncertainty: The art of breaking and making. Issue 1 (1st March 2016) - Squier, Joseph
Falling into art-making by accident introduced me to an image-world of symbol, metaphor and meaning. As a practising artist, I have been able to explore openended possibilities, and discover the deep beauty of ambiguity and the unknown. As a teacher of mostly non-art majors, I have been given the opportunity to share this fragment of my autobiography, and have discovered a diverse audience of students hungry for complex and nuanced challenges that develop their abilities to see, feel and intuit. My classroom acknowledges and explicitly values these fundamental human qualities, and for many students offers an antidote to an education that otherwise appears to value only quantification and instrumentality.